Towards the development of species-specific fish production models for small reservoirs in Southern Africa - Potts, Warren M (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2004)
The fish populations in small southern African reservoirs are largely unexploited and there is potential for fisheries development. However, the development of sustainable fisheries requires reliable estimates of potential yield or production. Empirical models that have been developed to predict fish production only apply to large water bodies and only predict total fish production, not the production of individual species. Small reservoirs generally have few commercially important species and therefore species-specific fish production models are an alternative approach. The small reservoirs of the Eastern Cape are dominated by the moggel (Labeo umbratus). The principal objectives of this thesis were to gain an understanding of the ecology of small reservoirs and the function of moggel in these systems. This information was used to design a research approach to rapidly develop species-specific models for small reservoirs in southern Africa. The limnology of two small reservoirs was compared. During the study period the reservoirs were turbid and showed a warm, monomictic pattern of thermal stratification. Anthropogenic pressure in the reservoir catchments appeared to be the overriding factor increasing the nutrient input to the reservoirs and consequently, influencing the biomass of algae in the reservoirs. The feeding biology of moggel in Katriver and Laing reservoirs was examined. Moggel are detrivorous and successfully digested diatoms. The slower growth rate of moggel in Katriver reservoir was attributed to the poorer nutritional value of the diet as a consequence of the lower concentration of diatoms in the detrital aggregate. The reproductive characteristics of moggel were examined in four reservoirs. Moggel were able to reproduce successfully in the reservoirs. This could be attributed to their r-selected reproductive strategy, with a high fecundity and an extended spawning season and their ability to spawn in a floodplain environment. Differences in recruitment success between years were found to be a consequence of the timing and duration of seasonal rains. The number of mature females in a population and the availability of suitable spawning habitat influenced recruitment success. The life history of the moggel in five reservoirs was compared. Growth appeared to be related to food availability, while mortality was lower in the populations where food was abundant and there were less predatory species. Size and age at maturity were not affected by environmental factors, but were dependent on growth and mortality. Three contrasting methods were used to estimate moggel gillnet selectivity. The Sechin, direct fyke net method and length-structured model all yielded similar results and correction factors obtained from the selectivity study were applied to the gillnet data to estimate the fish population size and structure in each reservoir. Using information from the life history and selectivity studies, the biomass and production of five moggel populations was estimated and related to abiotic and biotic factors in the reservoirs and their catchments. Moggel biomass and production was dependent on the biomass of algae, which was dependent on morphoedaphic characteristics of the reservoirs. Small, shallow reservoirs with a reasonable amount of human habitation in their catchments would sustain the highest algal biomass and provided they had adequate spawning habitat would also have the highest moggel biomass and production. The future research requirements for small reservoir fisheries are outlined and include a three-year program to develop a species-specific production model for any of the dominant species.
Keywords: Freshwater fishes -- Africa, Southern Fish populations -- Africa, Southern Fisheries -- Africa, Southern; Sustainable fisheries -- Africa, Southern Labeo -- Reproduction Cyprinidae -- Africa, Southern